Oceans and climate change adaptation: tracking international law and policy developments and challenges - Engler, Cecilia; VanderZwaag, David L.; Seck, Sara L. (Frontiers in Marine Science, 2025)
Climate change threatens the conservation of marine biodiversity, the sustainable use of marine resources, and the human rights of all people, especially those communities that depend on the marine environment for their livelihoods and culture. Sustained, coordinated and ambitious adaptation action is urgently needed. However, adaptation obligations and commitments for the oceans and the ocean economy have largely been addressed within traditionally siloed international regimes. This paper tracks these obligations and commitments by reviewing agreements, decisions and recommendations adopted under five main streams of international law and policy development: climate change, the law of the sea, fisheries and aquaculture, nature conservation, and human rights. The paper focuses on the obligations and commitments of States in two important areas: supporting the resilience of marine ecosystems; and facilitating the adaptation of the fisheries and aquaculture sectors, as representative economic sectors that contribute to food security and sustainable and traditional livelihoods. Through the assessment and review of relevant material, trends, synergies, and challenges have been identified. The paper highlights the evolving content of international law and policy on ocean-based adaptation to climate change. It identifies promising avenues for strengthening the coordination and coherence of ocean-based adaptation, including through the use of common principles, management tools and coordination mechanisms. It also identifies persistent challenges, including implementation gaps, lack of political will, and the complex conceptualization and implementation of adaptation law. The paper concludes by outlining key developments that could facilitate faster and bolder action by States.